2011
DOI: 10.1111/j.1460-9568.2011.07757.x
|View full text |Cite
|
Sign up to set email alerts
|

The antidepressant fluoxetine but not citalopram suppresses synapse formation and synaptic transmission between Lymnaea neurons by perturbing presynaptic and postsynaptic machinery

Abstract: Depression is a debilitating mental disorder, and selective serotonin reuptake inhibitors (SSRIs) constitute the first-line antidepressant treatment choice for the clinical management of this illness; however, the mechanisms underlying their therapeutic actions and side effects remain poorly understood. Here, we compared the effects of two SSRIs, fluoxetine and citalopram, on synaptic connectivity and the efficacy of cholinergic synaptic transmission between identified presynaptic and postsynaptic neurons from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…It should be noted however that recent studies suggest that fluoxetine’s spectrum of pharmacological activities in the Lymnaea nervous system extends beyond the compound’s “classical SSRI activity. [26,49]. Therefore, further studies are required to examine the mechanisms through which fluoxetine ameliorates the effects of age on neural- and behavioural plasticity in this model system.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted however that recent studies suggest that fluoxetine’s spectrum of pharmacological activities in the Lymnaea nervous system extends beyond the compound’s “classical SSRI activity. [26,49]. Therefore, further studies are required to examine the mechanisms through which fluoxetine ameliorates the effects of age on neural- and behavioural plasticity in this model system.…”
Section: Discussionmentioning
confidence: 99%
“…These trophic factor-mediated intracellular Ca 2+ oscillations required for excitatory synapse formation were inhibited in the presence of fluoxetine, indicating that fluoxetine prevents the expression of proteins involved in synaptogenesis (Xu et al, 2010). Attesting to this, we found that the expression and synaptic localization of synaptophysin, a synaptic vesicle-associated protein and presynaptic biomarker, were significantly reduced in synapses formed in the presence of fluoxetine, but not citalopram (Getz et al, 2011). Importantly, we also demonstrated that the inhibitory effect of fluoxetine on synapse formation is reversible following prolonged drug washout, and that this recovery is dependent on protein synthesis -that is, new synapses developed following the removal of fluoxetine.…”
Section: Fluoxetine But Not Citalopram Inhibits Synapse Formationmentioning
confidence: 56%
“…Furthermore, ratiometric Ca 2+ imaging revealed that the influx of Ca 2+ during action potential burst firing was significantly reduced by both fluoxetine and citalopram, suggesting that a loss of depolarizing driving force (i.e. through the inhibition of sodium and/or potassium channels and the development of action potential clamping) and subsequent indirect reduction in Ca 2+ entry is most likely responsible for the citalopram-mediated reduction of synaptic transmission (Getz et al, 2011). In Lymnaea neurons, the mechanism underlying the short-term plasticity of PTP has been shown to involve presynaptic Ca 2+ entry through voltage-gated calcium channels and subsequent activation of CaMKII, a protein kinase that mediates the effects of intracellular signalling cascades (Luk et al, 2011).…”
Section: Acute Exposure To Fluoxetine and Citalopram Affects Transmismentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the discussion regarding the symptoms seen after antidepressants are withdrawn, known as the antidepressant discontinuation syndrome, have focused on psychiatric and physical symptoms such as irritability, anxiety, agitation, sweating, tremor or trembling, insomnia, mouth movements, gastrointestinal symptoms and others. [60] Chronic fluoxetine has been reported to reduce the number of synapses in the brains of rats. However, this is a product of the preconception that a de-pressive syndrome would represent a relapse or recurrence, not withdrawal.…”
Section: Discussionmentioning
confidence: 99%